Comparative analysis of mitochondrial genomes of Schisandra repanda and Kadsura japonica - Lee, Hyo Ju; Lee, Yi; Lee, Sang-Choon; Kim, Chang-Kug; Kang, Ji-Nam; Kwon, Soo-Jin; Kang, Sang-Ho (Frontiers in Plant Science, 2023)
The family Schisandraceae is a basal angiosperm plant group distributed in East and Southeast Asia and includes many medicinal plant species such as Schisandra chinensis. In this study, mitochondrial genomes (mitogenomes) of two species, Schisandra repanda and Kadsura japonica, in the family were characterized through de novo assembly using sequencing data obtained with Oxford Nanopore and Illumina sequencing technologies. The mitogenomes of S. repanda were assembled into one circular contig (571,107 bp) and four linear contigs (10,898-607,430 bp), with a total of 60 genes: 38 protein-coding genes (PCGs), 19 tRNA genes, and 3 rRNA genes. The mitogenomes of K. japonica were assembled into five circular contigs (211,474-973,503 bp) and three linear contigs (8,010-72,712 bp), with a total of 66 genes: 44 PCGs, 19 tRNA genes, and 3 rRNA genes. The mitogenomes of the two species had complex structural features with high repeat numbers and chloroplast-derived sequences, as observed in other plant mitogenomes. Phylogenetic analysis based on PCGs revealed the taxonomical relationships of S. repanda and K. japonica with other species from Schisandraceae. Finally, molecular markers were developed to distinguish between S. repanda, K. japonica, and S. chinensis on the basis of InDel polymorphisms present in the mitogenomes. The mitogenomes of S. repanda and K. japonica will be valuable resources for molecular and taxonomic studies of plant species that belong to the family Schisandraceae.